Expropriation Risk Through Real Earnings Management on Islamic Banking - Surifah, Surifah (UI Scholars Hub, 2015)
This study develops a model of expropriation through real earnings management (REM) in the Indonesian Islamic banking industry. The purpose of this study is to test a new model by examining the relationship between REM, bank ownership types, and performance of Islamic banks in Indonesia in the period of 2006 - 2013. This study finds that there are significant differences in REM and performance scores in banks with different ownership types. The REM and performance scores for family-owned banks and private-owned banks are relatively similar. However, Islamic banks with government as the controlling shareholder have the highest REM scores and the lowest performance scores. In contrast, foreign-owned banks have the lowest REM scores and the highest performance scores. The indications of expropriation can be seen from the magnitude of REM. A high REM can lower profitability and efficiency while increasing the risks faced by Islamic banks in Indonesia.